The course of love - De Botton, Alain (London : Penguin Books, 2017)
Twenty years after his bestselling debut Essays in Love, internationally acclaimed author Alain de Botton returns to fiction with a brilliant new novel about modern relationships What does it mean to live happily ever after? At dinner parties and over coffee, Rabih and Kirsten's friends always ask them the same question: how did you meet? The answer comes easily- - it's a happy story, one they both love to tell. But there is a second part to this story, the answer to a question their friends never ask: what happened next? Rabih and Kirsten find each other, fall in love, get married. Society tells us this is the end of the story. In fact, it is only the beginning. From the first thrill of lust, to the joys and fears of real commitment, to the deep problems that surface slowly over two shared lifetimes, this is the story of a marriage. It is the story of modern relationships and how to survive them. Playful, wise and profoundly moving, The Course of Love is a delightful return to the novel by Alain de Botton, twenty years after his debut Essays in Love.
Keywords: Man-woman relationships -- Fiction; Marriage -- Fiction; Married people -- Fiction